Rhizoctonia species and anastomosis groups isolated from Lavandula species in Isparta, Türkiye - Cafer Eken; Dudu Demir (European Journal of Biological Research)
The genus Rhizoctonia includes a wide host of various kinds of more than 200 species of plants, and the genus includes different groups that are destructive plant pathogens and nonpathogenic to plants. Lavandula species are aromatic and medicinal plants in the family Lamiaceae. In this study, Rhizoctonia species were isolated from diseased Lavandula angustifolia and Lavandula x intermedia plants exhibiting symptoms related to crown and root rot to determine the anastomosis groups (AGs) of these isolates through hyphal anastomosis utilizing the test strains and the sequence analysis of the ribosomal DNA internal transcribed spacer (ITS) region. The obtained data confirmed the species identity of 29 isolates out of 44 as R. solani AG 4 HG-II and the remaining 15 isolates as binucleate Rhizoctonia (Ceratobasidium sp.) AG-K. Pathogenicity tests showed that AG 4 HG-II isolates were highly virulent on lavender plants, but AG-K isolates were not pathogenic. To our knowledge, this is the first report of the occurrence of R. solani AG 4 HG-II and binucleate Rhizoctonia (Ceratobasidium sp.) AG-K on L. angustifolia and L. x intermedia in Türkiye and around the world.